A Simple Light Stimulation of Caenorhabditis elegans. Issue 1 (1st February 2016) - Lee, Kun He; Aschner, Michael
Abstract: Response via noxious stimulus can be an important indicator of sensory neuron function and overall health of an organism. If the stimulation is quick and simple, and the animal can be rescued afterwards, such a method not only allows for assays pertaining to changed sensory ability after various treatments, but also increases the reliability of the statistical relationships that are established. This protocol demonstrates a stimulation assay in Caenorhabditis elegans, using blue light from common laboratory equipment: the fluorescent microscope. The nematode detects blue light using a set of amphid ciliary sensory neurons, and blue light is detrimental to its overall health after a prolonged exposure. However, under brief exposure, blue light stimulation provides a rapid and easy method for quantifying sensory functions and health without harming the animal. © 2016 by John Wiley & Sons, Inc.